Mitochondrial Nitric Oxide Synthase:A Masterpiece of Metabolic Adaptation, Cell Growth, Transformation, and Death - Finocchietto, Paola Vanesa (2009)
Mitochondria are specialized organelles that control energy metabolism and also activate a multiplicity of pathways that modulate cell proliferation and mitochondrial biogenesis or, conversely, promote cell arrest and programmed cell death by a limited number of oxidative or nitrative reactions. Nitric oxide (NO) regulates oxygen uptake by reversible inhibition of cytochrome oxidase and the production of superoxide anion from the mitochondrial electron transfer chain. In this sense, NO produced by mtNOS will set the oxygen uptake level and contribute to oxidation-reduction reaction (redox)?dependent cell signaling. Modulation of translocation and activation of neuronal nitric oxide synthase (mtNOS activity) under different physiologic or pathologic conditions represents an adaptive response properly modulated to adjust mitochondria to different cell challenges.